Targeting resolution of neuroinflammation after ischemic stroke with a lipoxin A4 analog: Protective mechanisms and long‐term effects on neurological recovery. Issue 5 (12th April 2017) - Hawkins, Kimberly E.; DeMars, Kelly M.; Alexander, Jon C.; de Leon, Lauren G.; Pacheco, Sean C.; Graves, Christina; Yang, Changjun; McCrea, Austin O.; Frankowski, Jan C.; Garrett, Timothy J.; Febo, Marcelo; Candelario‐Jalil, Eduardo
Abstract: Background: Resolution of inflammation is an emerging new strategy to reduce damage following ischemic stroke. Lipoxin A4 (LXA4 ) is an anti‐inflammatory, pro‐resolution lipid mediator that reduces neuroinflammation in stroke. Since LXA4 is rapidly inactivated, potent analogs have been synthesized, including BML‐111. We hypothesized that post‐ischemic, intravenous treatment with BML‐111 for 1 week would provide neuroprotection and reduce neurobehavioral deficits at 4 weeks after ischemic stroke in rats. Additionally, we investigated the potential protective mechanisms of BML‐111 on the post‐stroke molecular and cellular profile. Methods: A total of 133 male Sprague‐Dawley rats were subjected to 90 min of transient middle cerebral artery occlusion (MCAO) and BML‐111 administration was started at the time of reperfusion. Two methods of week‐long BML‐111 intravenous administration were tested: continuous infusion via ALZET ® osmotic pumps (1.25 and 3.75 μg μl −1  hr −1 ), or freshly prepared daily single injections (0.3, 1, and 3 mg/kg). We report for the first time on the stability of BML‐111 and characterized an optimal dose and a dosing schedule for the administration of BML‐111. Results: One week of BML‐111 intravenous injections did not reduce infarct size or improve behavioral deficits 4 weeks after ischemic stroke. However, post‐ischemic treatment with BML‐111 did elicit early protective effects as demonstrated by a significant reduction in infarct volume and improved sensorimotor function at 1 week after stroke. This protection was associated with reduced pro‐inflammatory cytokine and chemokine levels, decreased M1 CD40+ macrophages, and increased alternatively activated, anti‐inflammatory M2 microglia/macrophage cell populations in the post‐ischemic brain. Conclusion: These data suggest that targeting the endogenous LXA4 pathway could be a promising therapeutic strategy for the treatment of ischemic stroke. More work is necessary to determine whether a different dosing regimen or more stable LXA4 analogs could confer long‐term protection. Abstract : Post‐ischemic treatment with BML‐111, a lipoxin A4 receptor agonist, reduces brain injury and improves sensory function following ischemic stroke in rats. Activation of the lipoxin A4 resolution pathway with BML‐111 conferred protection by reducing pro‐inflammatory cytokine and chemokine levels, decreasing M1 CD40+ macrophages, and increasing alternatively activated, anti‐inflammatory M2 microglia/macrophage cell populations in the post‐ischemic brain.